Firm market valuation and intellectual property assets - Mafini Dosso; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2017)
This paper investigates the relationship between the innovative activity of the top corporate R&D investors worldwide and their valuation on the financial markets. The empirical analysis is based on a sample of more than 1,500 top publicly listed Multinational Corporations (MNCs) performing a considerable share of the business investment in R&D worldwide. The main dataset covers their intellectual properties, patents and trademarks, filed between 2005 and 2012. The paper extends upon the recent literature on the links between IP assets and the firms' financial valuation. It assesses the potential premium resulting from the interactive use of different IPRs. More importantly, it differentiates the extent to which IPRs confer a market premium to companies with respect to their industrial competitors from the extent to which within-company variations hold the key to a market premium. Finally confirming the relevance of corporate mixes of IP assets, important industrial specificities are found in the premiums granted to both individual and two-ways strategies.
Keywords: O31; O34; L19; 330; patents; trademarks; innovation; market valuation; within-/between-effects